A Comparison of Dobutamine, Norepinephrine, Vasopressin, and Hetastarch for the Treatment of Isoflurane-Induced Hypotension in Healthy, Normovolemic Dogs - Natalia Henao-Guerrero; Carolina H. Ricco-Pereira; Vaidehi V. Paranjape (Animals, 2023)
Isoflurane is a commonly used inhalation anesthetic in species undergoing veterinary care that induces hypotension, impacting organ perfusion, making it imperative to minimize its occurrence or identify effective strategies for treating it. This study evaluated and compared the hemodynamic effects of DOB, NEP, VAS, and HES in twelve isoflurane-anesthetized Beagle dogs. The order of the first three treatments was randomized. HES was administered last. Data were collected before treatments (baseline) and after 10 min of a sustained MAP of <45 mmHg induced by a high end-tidal isoflurane concentration (T0). Once treatment was initiated and the target MAP was achieved (65 to 80 mmHg) or the maximum dose reached, data were collected after 15 min of stabilization (T1) and 15 min after (T2). A 15 min washout period with a MAP of ≥65 mmHg was allowed between treatments. The intravenous dosage regimens started and were increased by 50% every five minutes until the target MAP or maximum dose was reached. The dosages were as follows: DOB, 5–15 μg/kg/min; NEP, 0.1–2 μg/kg/min; VAS, 0.5–5 mU/kg/min; and HET, 6% 1–20 mL/kg/min. DOB improved CO, DO2, and VO2, but reduced SVR. VAS elevated SVR, but decreased CO, DO2, and VO2. HES minimally changed BP and mildly augmented CO, DO2, and VO2. These treatments failed to reach the target MAP. NEP increased the arterial BP, CO, MPAP, and PAWP, but reduced HR. Norepinephrine infusion at 0.44 ± 0.19 μg/kg/min was the most efficient therapy for correcting isoflurane-induced hypotension.